Sustainable building material: using organic matter focusing on ceiling - Mohd Zulkifly Mohd Shariff (Penerbit Universiti Malaysia Perlis, 2011)
Sustainable development is development that meets the needs of the present without compromising the ability of future generation to meet their own needs (World Commission on Environment and Development, 1987). Agriculture waste such as rice straw and rice husk is produced as bio product of rice cultivate. Soil incorporation and field burning have been major practices for removing of rice straw but is now tightly regulated. Burning these agricultural wastes can lead to air pollution, thus causing global warming, ozone depletion and others. In addition, throwing this agricultural waste into the rivers or water body can cause water pollution that influenced on human health, animal health, agriculture and others. Thus, this project aims to reduce agricultural waste, with a quality product from this waste, thus can be commercialized in conventional and international trade. The product was tested in 4 parameters which are tensile strength, flexural strength, impact strength and swelling test (simulation & degradation). This study proved that for MDI ceiling board, tensile strength is 189.144 MPa, flexural strength is 52.63 MPa, impact strength is 4049.62 kJ/mp2s, percentage of simulation is 3.63% after 31 days and costing is RM 2.88/ftp2s. In addition, this product can also act as sound-absorbing agent and the agent of the reduction of internal heat, which will be reviewed in the future.